Decomposition of UML activity diagrams. (10th August 2017) - Chen, Huifeng; Jiang, Jian‐min; Hong, Zhong; Lin, Ling
Summary: In software engineering, UML activity diagrams in general can be useful for a modeling system functional behavior, ranging from the sequences of activities/actions from business processes within an organization or among organizations down to the detail of an algorithm. The stepwise refinement process makes activity diagrams more and more complex. To guarantee the behavior consistency and correctness under refinement, the activity diagrams must be decomposed according to the divide‐and‐conquer strategy. Traditional decomposition methods adopt manual techniques and cannot ensure the independence and completeness of the obtained subdiagrams. In this paper, a novel decomposition approach is proposed, which can automatically divide an activity diagram into atomic and correct subdiagrams (subdiagrams without abnormal behavioral problems) at the same level. When such an activity diagram specifies the whole functional behavior of a software system, the approach can in fact decompose a system into multiple atomic subsystems. Every atomic subsystem is a completely independent system. It may be independently developed, independently tested, and independently deployed. The method facilitates the management, development, and maintenance of a software system. With the help of a prototype tool, a case study demonstrates the decomposition method.